Hadis sebagai Pilar Kebebasan Beragama : Meningkatkan Kesadaran Toleransi di Kalangan Generasi Z dalam Konteks Global - Ola Alifiyanti Zahra Purnama; Endad Musaddad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the role of Hadith as a foundation for instilling the values of religious tolerance, with a focus on shaping the awareness of Generation Z in the contemporary era of technology and globalization. The Qur'an and the Hadith of Prophet Muhammad SAW emphasize respect for religious diversity and firmly prohibit intolerance, offering a strong theological basis for promoting harmonious coexistence. As a digitally active generation, Gen Z possesses significant potential to disseminate tolerance values through online platforms. Nevertheless, they face challenges such as disinformation, hate speech, and the spread of distorted religious interpretations, which may hinder the cultivation of inclusive attitudes. This research highlights that the integration of tolerance values requires methods aligned with Gen Z’s characteristics, including interactive discussions, the strategic use of social media, and educational approaches rooted in prophetic principles. By adopting such methods, religious teachings can be contextualized in a manner that resonates with Gen Z’s communication styles and digital literacy levels. The study employs a qualitative literature review to analyze relevant Hadith texts, their interpretations, and contemporary strategies for value transmission. The findings suggest that a combination of religious education, digital engagement, and community-based initiatives can effectively foster interfaith understanding and reduce intolerance among youth. Ultimately, this research offers a practical framework for educators, religious leaders, and policymakers to strengthen inter-religious tolerance by enhancing the comprehension and application of Hadith in addressing the unique challenges of the digital era.